Detection of Homologous Blood Transfusion in Sport Doping by Flow Cytofluorimetry: State of the Art and New Approaches to Reduce the Risk of False-Negative Results - Donati, Francesco; de la Torre, Xavier; Pagliarosi, Sarajane; Pirri, Daniela; Prevete, Giuliana; Botrè, Francesco (Frontiers in Sports and Active Living, 2022)
This paper presents the results of a study aimed to improve the effectiveness of the method for the detection of homologous blood transfusions in doping control. Two strategies have been followed to reduce the risk of false-negative results: (i) the monitoring of a broader range of erythrocytes surface antigens; and (ii) the application of different surface erythrocyte staining protocols, tailored on the different antigens and the type of antigenic mismatch that had to be detected (whether it is the donor or the recipient who expresses or not the antigen to be detected). Special attention has also been focused on the time factor, to avoid prolonged sample storage, since hemolysis may have a significant impact on the reliability and quality of the results. Our experimental evidence suggests that the risk of false-negative results can be minimized by (i) the expansion of the target antigen panel; (ii) a more accurate selection of the gating area of the red blood cells; (iii) the choice of a better fluorochrome to be conjugated to the secondary antibody; and (iv) the implementation of different staining protocols depending on the nature of the double population to be detected (donor expressing vs. recipient non-expressing and vice versa).